(25ln(5)-23ln(0))-(25ln(2)-23ln(3))=x

Simple and best practice solution for (25ln(5)-23ln(0))-(25ln(2)-23ln(3))=x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (25ln(5)-23ln(0))-(25ln(2)-23ln(3))=x equation:


Simplifying
(25ln(5) + -23ln(0)) + -1(25ln(2) + -23ln(3)) = x

Reorder the terms for easier multiplication:
(25 * 5ln + -23ln(0)) + -1(25ln(2) + -23ln(3)) = x

Multiply 25 * 5
(125ln + -23ln(0)) + -1(25ln(2) + -23ln(3)) = x

Reorder the terms for easier multiplication:
(125ln + -23 * 0ln) + -1(25ln(2) + -23ln(3)) = x

Multiply -23 * 0
(125ln + 0ln) + -1(25ln(2) + -23ln(3)) = x

Anything times zero is zero.
(125ln + 0ln) + -1(25ln(2) + -23ln(3)) = x

Reorder the terms:
(0 + 125ln) + -1(25ln(2) + -23ln(3)) = x
Remove the zero:
(125ln) + -1(25ln(2) + -23ln(3)) = x
(125ln) + -1(25ln(2) + -23ln(3)) = x

Reorder the terms for easier multiplication:
(125ln) + -1(25 * 2ln + -23ln(3)) = x

Multiply 25 * 2
(125ln) + -1(50ln + -23ln(3)) = x

Reorder the terms for easier multiplication:
(125ln) + -1(50ln + -23 * 3ln) = x

Multiply -23 * 3
(125ln) + -1(50ln + -69ln) = x

Combine like terms: 50ln + -69ln = -19ln
(125ln) + -1(-19ln) = x

Remove parenthesis around (-19ln)
(125ln) + -1 * -19ln = x

Multiply -1 * -19
(125ln) + 19ln = x

Combine like terms: (125ln) + 19ln = 144ln
144ln = x

Solving
144ln = x

Solving for variable 'l'.

Move all terms containing l to the left, all other terms to the right.

Divide each side by '144n'.
l = 0.006944444444n-1x

Simplifying
l = 0.006944444444n-1x

See similar equations:

| 5t=1.905 | | 24=23x-15x | | -7a=-385 | | -8-w=11 | | 200=b+6 | | -7x-2=24--9 | | p+25=43 | | -8+10w=11w+11 | | 2(x+4)=-11 | | 2=172 | | 42x^2+31x-17=0 | | -c+4=-35 | | 2-b=18 | | 2-18=20 | | (9x+7)(9x+7)=0 | | -16t^2+12t+4=0 | | 2(7x-2)(4x+3)=0 | | 4x^2+31x-17=0 | | -3+15v=-63 | | 4x^2+31x-19=2 | | 0=500n-2000 | | 16xy+28x+12y+21= | | -9r^3(7r^2+6)(7r^2-6)=0 | | 32w+8= | | x^2=-4x-20 | | -14x-14=2x+7 | | 4x^2+20x+19=6 | | 4y^4(2y+1)(y-6)=0 | | 3v^2+20+32=0 | | x^2+5=42 | | (3a-3d)(3a+2d)=0 | | 9+x=-125 |

Equations solver categories